Evaluating integrated surveillance of antimicrobial resistance: experiences from use of three evaluation tools. (December 2020) - Nielsen, Liza Rosenbaum; Alban, Lis; Ellis-Iversen, Johanne; Mintiens, Koen; Sandberg, Marianne
Abstract: Background: Integrated antimicrobial resistance (AMR) surveillance programmes require regular evaluation to ensure they are fit for purpose and that all actors understand their responsibilities. This will strengthen their relevance for the clinical setting, which depends heavily on continued access to effective treatment options. Several evaluation tools addressing different surveillance aspects are available. Objectives: The aim was to understand the strengths and weaknesses of three evaluation tools, and to improve guidance on how to choose a fit-for-purpose tool. Sources: Three tools were assessed: (a) AMR-PMP—the Progressive Management Pathway tool on AMR developed by the Food and Agriculture Organization (FAO) of the United Nations, (b) NEOH developed by the EU COST Action 'Network for Evaluation of One Health' and (c) SURVTOOLS developed in an FP7-EU project 'RISKSUR'. Each tool was assessed with regard to contents, required evaluation processes including stakeholder engagement and resource demands, integration coverage across relevant sectors and applicability. They were compared using a predefined scoring scheme and a strengths–weaknesses–opportunities–threats (SWOT)-like format for commenting. Content: All three tools address multiple decision-making levels and aspects of stakeholder engagement. NEOH focuses on system features, learning, sharing, leadership and infrastructure, and requires a description of the underlying system in which AMR develops. AMR-PMP focuses on four areas: awareness, evidence, governance and practices and assesses the implementation degree of pre-chosen aspects within these areas. This requires less of the evaluator, but warrants participation of multiple stakeholders. SURVTOOL provides information and references on how to evaluate effectiveness, process and comprehensiveness of surveillance programmes. All three tools require veterinary epidemiology expertise and varying levels of evaluation methodology training to use appropriately. Implications: The tools covered AMR surveillance and One Health aspects to varying degrees. This study provides guidance on aspects to consider when choosing between available tools and embarking on an evaluation of integrated surveillance.